2021
DOI: 10.1186/s13054-021-03856-3
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of trained ICU doulas providing early psychological support to critically ill patients

Abstract: Background Over a third of critical illness survivors suffer from mental health problems following hospitalization. Memories of delusional experiences are a major risk factor. In this project, ICU doulas delivered a unique positive suggestion intervention targeting the vulnerable time period during critical illness when these memories are formed. Methods Adult critically ill patients were recruited for this single-arm, prospective pilot study. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…More than one‐third of critical illness survivors struggle with post‐intensive care syndrome following hospitalization, which is characterized by anxiety, depression, and cognitive and physical impairments. Many interventions have been reported to improve psychological outcomes, including ICU diaries, music therapy, nurse‐led consultations, nurse‐led preventive psychological intervention, and mindfulness training 11 . In this case, the patient appeared slightly anxious and nervous on the first day in the ICU, naturally worrying about her newborn and herself.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…More than one‐third of critical illness survivors struggle with post‐intensive care syndrome following hospitalization, which is characterized by anxiety, depression, and cognitive and physical impairments. Many interventions have been reported to improve psychological outcomes, including ICU diaries, music therapy, nurse‐led consultations, nurse‐led preventive psychological intervention, and mindfulness training 11 . In this case, the patient appeared slightly anxious and nervous on the first day in the ICU, naturally worrying about her newborn and herself.…”
Section: Discussionmentioning
confidence: 92%
“…Many interventions have been reported to improve psychological outcomes, including ICU diaries, music therapy, nurse-led consultations, nurse-led preventive psychological intervention, and mindfulness training. 11 In this case, the patient appeared slightly anxious and nervous on the first day in the ICU, naturally worrying about her newborn and herself. Subsequently, the pain increased her anxiety.…”
Section: Pain Care Based On Psychological Supportmentioning
confidence: 84%
“…In addition, it has been suggested that the psychological status of critically ill patients might affect the treatment outcomes ( 18 , 19 ) and also considered that the surrounding physical environmental stimulation devices such as lights and alarms present in the ICU environment may further lead to psychological problems such as anxiety and fear ( 20 , 21 ). As a part of psychological support, positive encouragement during mobilization interventions and improvement of one's abilities by maintaining self-confidence to achieve a better recovery might play a key role in a patient's recovery ( 22 , 23 ). The ICF-based progressive mobilization protocol has not only included environmental adjustments like day/night alternating light adjustment and alarm tone size setting but also provided videos recorded by family members or out of patients' usual interest, which may influence the patient's psychological state.…”
Section: Discussionmentioning
confidence: 99%
“…Although the need for intensive care doulas was identified in 2017, 19 the need was intensified by the rapid deterioration of life for those facing COVID-19 as well as other serious illnesses. 20,21 A study was initiated specifically to provide early psychological support for the critically ill. Doulas were trained to respond to the specific needs of the critical care patient-to understand more about policies and procedures in this setting, to provide comfort and support through soothing conversation, and to explain what to expect and to take the time to address whatever concerns the patient had in support of the busy nurse: in other words, this intervention was created to humanize the critically ill experience. 20 Anxiety reduction was notable.…”
Section: Intensive Care Unit Doulasmentioning
confidence: 99%